2014
DOI: 10.1111/tpj.12679
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of stress‐responsive lncRNAs in Arabidopsis thaliana by integrating expression, epigenetic and structural features

Abstract: These authors contributed equally to this work. SUMMARYRecently, in addition to poly(A)+ long non-coding RNAs (lncRNAs), many lncRNAs without poly(A) tails, have been characterized in mammals. However, the non-polyA lncRNAs and their conserved motifs, especially those associated with environmental stresses, have not been fully investigated in plant genomes. We performed poly(A)À RNA-seq for seedlings of Arabidopsis thaliana under four stress conditions, and predicted lncRNA transcripts. We classified the lncRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
215
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 296 publications
(233 citation statements)
references
References 70 publications
16
215
2
Order By: Relevance
“…3D), which was also a feature of noncoding RNAs (Cabili et al 2011;Liu et al 2012;Pauli et al 2012;Sun et al 2013;Di et al 2014). Taken together, these results demonstrated that the extended 3 ′ UTRs had characteristics of long noncoding RNAs, raising the possibility that they might function as noncoding RNAs.…”
Section: Extended 3 ′ Utrs Have Characteristics Of Long Noncoding Rnasmentioning
confidence: 64%
See 1 more Smart Citation
“…3D), which was also a feature of noncoding RNAs (Cabili et al 2011;Liu et al 2012;Pauli et al 2012;Sun et al 2013;Di et al 2014). Taken together, these results demonstrated that the extended 3 ′ UTRs had characteristics of long noncoding RNAs, raising the possibility that they might function as noncoding RNAs.…”
Section: Extended 3 ′ Utrs Have Characteristics Of Long Noncoding Rnasmentioning
confidence: 64%
“…Recently, a large group of long noncoding RNAs, including lincRNAs and long noncoding natural antisense transcripts (lncNATs), have been characterized in Arabidopsis (Liu et al 2012;Zhu et al 2013;Di et al 2014;Wang et al 2014). We found that the extended 3 ′ UTRs also had characteristics of long noncoding RNAs.…”
Section: Extended 3 ′ Utrs Have Characteristics Of Long Noncoding Rnasmentioning
confidence: 92%
“…Subsequently, the annotated (known) and predicted novel lncRNAs were filtered and classified based on their genomic locations. They were subtyped into antisense, intronic, ambiguous, and intergenic ncRNAs (Di et al 2014). To remove the ambiguity, we only retained intergenic lncRNAs (i.e., lincRNAs) for further studies.…”
Section: Curation Of Known and Novel Lncrnas In Flymentioning
confidence: 99%
“…Different approaches have been used to identify the genome wide lncRNAs in plants, and thousands of lncRNAs have been identified in Arabidopsis [9][10][11][12][13][14][15][16][17][18], rice [19][20][21][22], maize [23][24][25], Medicago [26], Brassica [27], Populus trichocarpa [28], wheat [29] and apple [30] (Table 1). Tiling array was used as a large-scale tool for identifying new transcripts in Arabidopsis before the Next-Generation Sequencing (NGS) technology was applied, and many lncRNAs had been found in this way.…”
Section: Genome Wide Identification Of Different Types Of Lncrnas In mentioning
confidence: 99%